(3GdEbJUGO GdeUQj bVGjG heTcdGJ (B/s - (3bGHd, eMeO UahJs ([(3Ohf ecGf(B]: s [(3Ohf fGTQ(B], s, 2008)
(3jVe GdEbJUGO GdeUQj, fgQ Gdfjd hGdNdGa Mhd MUI eUQ ef eGgjI , GdSjGSGJ GdEbJUGOjI , GdEUdGM GdEbJUGOjs
Keywords: (3GdEbJUGOs; (3GdJNWjW GdEbJUGOj(B- (3eUQs; (3GdSjGSI GdEbJUGOjI(B- (3eUQs; (3eUQ(B- (3GdEbJUGOs